IDENTIFICATION OF MASS TRANSFER PARAMETERS FOR ROCK SALT DISSOLUTION IN A PLUG FLOW SYSTEM - FOGARASI, Szabolcs; NAGY, Melinda; IMRE-LUCACI, Florica; IMRE-LUCACI, Arpad (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Considering the particularities of rock salt solution mining, the current paper aims to determine the mass transfer parameters for rock salt dissolution in a plug flow system. The influence of crucial operating parameters such as flow rate and channel depth on the mean driving force, volumetric mass transfer coefficient and extraction yield was evaluated. It was found that flow rate increase intensifies the dissolution process leading to a more rapid dissolution of the rock salt deposit. Similar effect was noticed in the case of flow channel depth increase which leads to higher mass transfer area, increasing the amount of dissolved salt from the rock salt deposit.